Protein-Based Electronic Skin Akin to Biological Tissues - Jo, Minsik; Min, Kyungtaek; Roy, Biswajit; Kim, Sookyoung; Lee, Sangmin; Park, Ji Yong; Kim, Sunghwan (ACS Nano, 2018)
Human skin provides an interface that transduces external stimuli into electrical signals for communication with the brain. There has been considerable effort to produce soft, flexible, and stretchable electronic skin (E-skin) devices. However, common polymers cannot imitate human skin perfectly due to their poor biocompatibility, biofunctionality, and permeability to many chemicals and biomolecules. Herein, we report on highly flexible, stretchable, conformal, molecule-permeable, and skin-adhering E-skins that combine a metallic nanowire (NW) network and silk protein hydrogel. The silk protein hydrogels offer high stretchability and stability under hydration through the addition of Ca2+ ions and glycerol. The NW electrodes exhibit stable operation when subjected to large deformations and hydration. Meanwhile, the hydrogel window provides water and biomolecules to the electrodes (communication between the environment and the electrode). These favorable characteristics allow the E-skin to be capable of sensing strain, electrochemical, and electrophysiological signals.
Keywords: Biofunctionality; Biological tissues; Electrical signal; Electrophysiological signals; External stimulus; Metallic nanowires; Stable operation; Stretchable electronics; Animals; Bombyx; Electrochemical Techniques; Electrodes; Hydrogel, Polyethylene Glycol Dimethacrylate; Nanowires; Silk; Wearable Electronic Devices; electronic skin; hydrogel electronic device; silk protein; stretchable; water permeability